EP.FRI.103 Acute Appendicitis in an Amyand Hernia – a case report and literature review. (28th October 2021) - Ahmad, Manal; Fazili, Noureen; Chang, Tou-Pin; Abdalla, Hashim; Watfah, Josef; Leo, Cosimo Alex
Abstract: Introduction: An Amyand Hernia (AH) is the presence of an Appendix within an Inguinal Hernia. We present here our clinical management of acute appendicitis in an AH and subsequent literature review. A 73 year old male patient presented with a two day history of right sided irreducible inguinoscrotal hernia with tender swelling on standing and walking. This was not associated with symptoms of bowel obstruction or fevers. Blood investigations revealed a raised C-Reactive Protein of 129m/l and White Cell Count of 15x 10^9/L. A Computed Tomography scan of the Abdomen and Pelvis revealed a right sided inguinoscrotal hernia arising lateral to the inferior epigastric vessels, containing an inflamed appendix and omental fat. The patient underwent an emergency open hernia repair with mesh and, considering that the appendix base was intra-abdominal, also underwent a laparoscopic appendicectomy. Method: We conducted a literature review on Pubmed and Medline using the MeSH terms 'Amyand Hernia' AND 'Appendicitis' from 1970-2020. Results: We longlisted 179 articles. Of these, 117 were excluded, as they were either paediatric cases, not relevant or mentioned in discussions. Finally, 62 relevant articles were included in the review. Conclusion: Acute Appendicitis in Amyand Hernias has an incidence of 0.07-0.13%. Most cases remain as incidental findings however, increased use of imaging techniques has allowed accurate diagnoses and attempts at classifications. There is also weak association with Situs Inversus and atypical appendiceal tumours including adenocarcinoma, carcinoid and neuroendocrine tumour. Their management varies according to the extent of inflammation, radiological and intraoperative findings.